Difference in Aneurysm Characteristics between Patients with Familial and Sporadic Aneurysmal Subarachnoid Haemorrhage - Mensing, Liselore A. (PLoS One, 2016)
OBJECT: Patients with familial intracranial aneurysms (IA) have a higher risk of rupture than patients with sporadic IA. We compared geometric and morphological risk factors for aneurysmal rupture between patients with familial and sporadic aneurysmal subarachnoid hemorrhage (aSAH) to analyse if these risk factors contribute to the increased rupture rate of familial IA. METHODS: Geometric and morphological aneurysm characteristics were studied on CT-angiography in a prospectively collected series of patients with familial and sporadic aSAH, admitted between September 2006 and September 2009, and additional patients with familial aSAH retrieved from the prospectively collected database of familial IA patients of our center. Odds ratios (OR) with corresponding 95% confidence intervals (95% CI) were calculated to compare the aneurysm characteristics between patients with familial and sporadic aSAH. RESULTS: We studied 67 patients with familial and 184 with sporadic aSAH. OR’s for familial compared with sporadic aSAH were for oval shape 1.16(95%CI:0.65–2.09), oblong shape 0.26(95%CI:0.03–2.13), irregular shape 0.83(95%CI:0.47–1.49), aspect ratio ≥ 1.6 0.94(95%CI:0.54–1.66), contact with the perianeurysmal environment (PAE) 1.15(95%CI:0.56–2.40), deformation by the PAE 1.05(95%CI:0.47–2.35) and for dominance of the posterior communicating artery (PCoA) in case of PCoA aneurysms 1.97(95% CI:0.50–7.83). CONCLUSIONS: The geometric and morphological risk factors for aneurysm rupture do not have a higher prevalence in familial than in sporadic aSAH and thus do not explain the increased risk of IA rupture in patients with familial IA. We recommend further search for other potential risk factors for rupture of familial IA, such as genetic factors.